Implementation of PID controller on prasmatic control of universal stretch and bending machine (USBM) simplified model - Mohd Afiq, Mat Noor (2008)
In this project, generally the project is about implementation of PID controller on prasmatic control of universal stretch and bending machine (USBM) simplified model. The focus on this project is to use a controller as the control algorithm to control the position and movement of servo pneumatic valve. Without controller, the servo pneumatic valve extend, retract and stop at the position that desire but the position that the servo pneumatic were stop not an exact position and the movement also not too smooth. To get the exact position and smooth movement, the method that was used is by using the controller. There are many types of controller that can be used as the control algorithm such as PID Controller, State Feedback Controller and LQR Controller. In this project, the PID Controller was used as the control algorithm to control the system. Generally, this project can be separated into 4 parts which are PLC Setup, PLC programming, PID controller and Output (Regulator and cylinder). The CJ1M CJ Series-CPU 12 type of PLC was used in this project. In this project, a controller will give a signal to regulator and the output (pneumatic valve) will move base on the signal that was given by the controller.